Gambaran Pengobatan Diare Akut Anak di Puskesmas Jiwan Madiun - Reni Ariastuti; Dunung Kusumawati (STIKES MUHAMMADIYAH KLATEN, 2020)
Diarrhea is a digestive tract disease with a consistency of loose stools and an increased frequency. The morbidity and mortality rates for children diarrhea in Indonesia still tend to be high. This study aims to determine the description of pharmacological therapy in the treatment of outpatients with acute diarrhea in Jiwan Public Health Center, Madiun by referring to the management of diarrhea therapy from the Ministry of Health. This research was conducted in a descriptive observational manner with retrospective data collection on outpatients with acute diarrhea at the Jiwan Public Health Center, Madiun in the Januri-June 2019 period. Sampling used a purposive sampling technique that met the inclusion criteria. The type of data used in this study is secondary data taken from patient medical records. Data analysis of the results of the study was carried out descriptively to determine the demographic distribution and treatment of patients with acute diarrhea in children at the Jiwan Public Health Center, Madiun. Most of the treatments had met the management of diarrhea. The percentage of drug use included using ORS as much as 29%, antidiarrheal attalpulgite and kaolin pectin by 26%, zinc 25%, anti-vomiting used by domperidone 7% and metochlopramide 4%, cotrimoxazole antibiotics 49% of the total cases 100% (75 cases). Evaluation of the dose of co-trimoxazole and zinc, there were 10% and 75% incorrect doses.